Correlation between Work Environment Control and P53 Level Among Dental Technicians - Puspa Dila Rohmaniar (Poltekkes Kemenkes Kupang, 2023)
Dental technicians cannot avoid being exposed to various physical, chemical, and biological agents due to their work environment. Therefore, technicians must control the work environment according to standard procedures to protect themselves from metal exposure in the workplace. Metal exposure can cause a decrease in the wild P53 gene. This study aims to determine the correlation between work environment control and wild P53 level among dental technicians. This was an analytic observational study with a cross sectional approach. There were 40 randomly selected samples. Data were derived through interviews and observation. Wild P53 was examined from saliva by indirect ELISA method. Data were analyzed using the Spearman correlation test with the significance value of p<0.05 (95% confidence level). The results showed that there was a significant correlation between work environment control and wild P53 level with a significance value of p<0.05. It was further obtained a Spearman's correlation value of 0.436. Such finding indicated a positive correlation value, meaning that the higher the score of work environment control performed by dental technicians while working on metal prostheses, the higher the P53wild level. It can be concluded that there was a significant correlation between work environment control and wild P53 level. The better and more correct the implementation of work environment control, the higher the wild P53 level. Future researchers are recommended to observe the effect of variables with other genotoxic markers on the effect of work environment controls among dental technicians.